Weighted Blankets as a Non-Pharmacological Intervention for Sleep, Mental and Neurodevelopmental Disorders: A Narrative Review - Jaślikowska, Adrianna; Niderla, Natalia; Rzeszutek, Jakub; Rachwał, Natalia; Grzyb, Weronika; Kurnik, Michał; Grzybowska, Dominika; Idzik, Kamil; Kubicki, Adrian (Journal of Education, Health and Sport, 2026)
Background: Weighted blankets are a non-pharmacological intervention based on deep pressure stimulation (DPS) that has gained increasing popularity as a supportive method for improving sleep, reducing anxiety, and enhancing daily functioning in individuals with mental and neurodevelopmental disorders. Despite their widespread use in both clinical and home settings, the evidence regarding their effectiveness remains inconsistent. Results: Available evidence suggests that weighted blankets are generally safe and well tolerated. Some studies indicate improvements in subjective sleep quality, insomnia severity, anxiety symptoms, and daytime functioning, particularly among individuals with insomnia co-occurring with anxiety or psychiatric disorders. However, findings regarding objective sleep parameters remain inconsistent. Evidence supporting the use of weighted blankets in ASD is limited, whereas preliminary findings in ADHD suggest potential benefits for sleep outcomes. Proposed mechanisms include modulation of autonomic nervous system activity, increased melatonin secretion, and effects on sensory processing, although these hypotheses require further confirmation. Conclusions: Current evidence does not support the routine use of weighted blankets as a standalone therapeutic intervention. Nevertheless, they may represent a safe and accessible adjunctive strategy for selected patients, particularly those experiencing insomnia and anxiety. Further high-quality studies employing objective outcome measures are needed to clarify their clinical effectiveness and mechanisms of action